2008
DOI: 10.1016/j.rapm.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Gross Anatomy of the Brachial Plexus Sheath in Human Cadavers

Abstract: We observed a macroscopic fibrous structure surrounding the plexus, which was filled with loose connective tissue lacking any apparent organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Franco et al in a recent cadaver study of the brachial plexus sheath described the membrane as only 1-to 2-mm thick and observed that the sheath could be easily detached from the surrounding muscle bed [10]. Our results suggest that local anaesthetic solution readily diffuses across this membrane, as both groups were equivalent in terms of onset of the sensory and motor block.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Franco et al in a recent cadaver study of the brachial plexus sheath described the membrane as only 1-to 2-mm thick and observed that the sheath could be easily detached from the surrounding muscle bed [10]. Our results suggest that local anaesthetic solution readily diffuses across this membrane, as both groups were equivalent in terms of onset of the sensory and motor block.…”
Section: Discussionsupporting
confidence: 53%
“…Anatomical literature suggests that a connective tissue sheath surrounds the brachial plexus as a thin membrane [9][10][11][12]. Franco et al in a recent cadaver study of the brachial plexus sheath described the membrane as only 1-to 2-mm thick and observed that the sheath could be easily detached from the surrounding muscle bed [10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not consider septae dividing the brachial plexus within the sheath. However, the presence of septae has not been confirmed, and it has been known LA permeates septae and distributes within sheaths [13,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…A paraneural sheath surrounds the brachial plexus as a thin membrane (10,12), and it is possible that the paraneural sheath precludes the need for direct circumferential injection. As the space between nerve roots is limited, the area becomes saturated with LA, and multiple injections force incoming LA molecules to find alternate paths of less resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to reduced systemic uptake of LA in the TI group, due to more LA being contained within the brachial plexus sheath, thus increasing the reservoir volume of LA solution (10). Franco et al (12) described the interior of the sheath surrounding the neuronal tissue as a combination of loose connective tissue and fat, with few veins running along the sheath interior. These observations potentially explain the results of the present study, as there may have been decreased systemic absorption of LA in the TI group due to reduced vascularity on the interior of the sheath.…”
Section: Discussionmentioning
confidence: 99%